Integral representation of the solutions to Heun's biconfluent equation - S. Belmehdi; J.-P. Chehab (Abstract and Applied Analysis)
First, we trace the genesis of the canonical form of Heun's biconfluent equation. Second, we present a method which allows us to find an integral expression as a solution to our equation, and finally, using the properties of Meijer G-functions, we give an integral representation of a fundamental system of solutions to the biconfluent equation.